Attitudes and the (dis)continuity between memory and imagination - Sant’Anna, André (Estudios de Filosofía, 2021)
The current dispute between causalists and simulationists in philosophy of memory has led to opposing attempts to characterize the relationship between memory and imagination. In a recent overview of this debate, Perrin and Michaelian (2017) have suggested that the dispute over the (dis)continuity between memory and imagination boils down to the question of whether a causal connection to a past event is necessary for remembering. By developing an argument based on an analogy to perception, I argue that this dispute should instead be viewed as a dispute about the nature of the attitudes involved in remembering and imagining. The focus on attitudes, rather than on causal connections, suggests a new way of conceiving of the relationship between memory and imagination that has been overlooked in recent philosophy of memory.